2001
DOI: 10.1046/j.1469-1809.2001.6520177.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and cancer incidence in persons with numerical sex chromosome abnormalities: a cohort study

Abstract: Mortality and cancer incidence were assessed in a cohort of 1373 patients with numerical sex chromosome abnormalities diagnosed at three cytogenetics centres in Britain during 1959-90, and were compared with expectations from national rates. Four hundred patients with Turner's syndrome were followed, of whom 62 died, with a relative risk (RR) of death of 4.16 (95 % confidence interval (CI) 3.22-5.39). Turner's syndrome patients had greatly raised risks of death from diseases of the nervous, cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
120
2
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(128 citation statements)
references
References 22 publications
3
120
2
3
Order By: Relevance
“…Extra X chromosome dosage seems to be an event also in male breast tumors, in which the lack of Y chromosome and the duplication of X were often reported (18,(20)(21)(22)(23)(24). The role of X chromosome dosage in breast tumor development is further strengthen by the evidence that males with a 47, XXY karyotype have a 50-fold increased risk to develop a breast cancer respect to 46,XY males (25,26).…”
Section: Introductionsupporting
confidence: 49%
“…Extra X chromosome dosage seems to be an event also in male breast tumors, in which the lack of Y chromosome and the duplication of X were often reported (18,(20)(21)(22)(23)(24). The role of X chromosome dosage in breast tumor development is further strengthen by the evidence that males with a 47, XXY karyotype have a 50-fold increased risk to develop a breast cancer respect to 46,XY males (25,26).…”
Section: Introductionsupporting
confidence: 49%
“…In addition, a total of 2 breast cancer deaths was observed. 23 Many medical textbooks and several case reports suggest an association between KS and leukemia and lymphoma; however, this association has not been proven. A cohort study of 696 men with KS found no difference in the incidence of leukemia and lymphoma.…”
Section: Medical Management and Surveillancementioning
confidence: 99%
“…1,35 Smoking cessation should be emphasized, not only to potentially prevent vascular complications arising from diabetes but also to prevent lung cancer, which contributes to increased overall mortality. 23 It has also been suggested that men with KS be evaluated for specific learning disabilities. 5 Although overall intelligence may be within normal range, it has been noted that KS patients tend to have deficits in verbal and motor skills.…”
Section: Medical Management and Surveillancementioning
confidence: 99%
See 2 more Smart Citations